Identifikasi Kandungan Kimia Daun Pohon Beringin (Ficus Benyamina L.) sebagai Obat Tradisional - Suaibatul Aslamiah; Haryadi Haryadi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
The purpose of this study is to determine the compounds secondary metabolites (alkaloids, tannins, saponins, flavonoids and steroids and terpenoids) contained in the leaves of the banyan tree and can provide therapeutic effects. This research performed at the Laboratory of the Faculty of Health Sciences University of Muhammadiyah Palangkaraya, from May to September 2013. The method used is an experiment to identify the compound, an active compound found anything on the leaves of the banyan tree. Identify the stages of phytochemical composition of the compounds which are present in the banyan tree covering an advance test that consisted of fixation loss on drying, determination of water-soluble extract, and the determination of the ethanol-soluble extract . Followed by the identification of phytochemicals include identification tannins, alkaloids, flavonoids, saponins, and steroids and terpenoids. Where in their identification using liquid extract and extract thick banyan tree was maceration for 24 hours using 95% ethanol for 3 (three) days. The results obtained in this phytochemical identification positive banyan tree contains tannin, saponin and alkaloid. Negative result in the identification of phytochemicals shows that the banyan tree do not contain flavonoid, steroids and terpenoids. Until the advent of the compound of alkaloids, saponins and tannins in the banyan tree are expected to later be used as the initial stages of the manufacture of traditional medicine.